2021
DOI: 10.1007/s00436-021-07307-4
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis drug development: from preclinical models to humans

Abstract: Twenty diseases are recognized as neglected tropical diseases (NTDs) by World Health Assembly resolutions, including human filarial diseases. The end of NTDs is embedded within the Sustainable Development Goals for 2030, under target 3.3. Onchocerciasis afflicts approximately 20.9 million people worldwide with > 90% of those infected residing in Africa. Control programs have made tremendous efforts in the management of onchocerciasis by mass drug administration and aerial larviciding; however, disease elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 163 publications
(153 reference statements)
1
9
0
Order By: Relevance
“…Epidemiological modelling suggests elimination efforts based exclusively on MDA will not achieve disease elimination [7], whilst the consensus amongst experts (~70%) is that additional measures are required to eliminate human onchocerciasis [8]. The recent licencing of the macrocyclic lactone moxidectin for use as an additional microfilaricidal treatment is promising [9][10][11], whilst efforts to identify and evaluate safe drugs targeting adult worms (macrofilaricides) are ongoing [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological modelling suggests elimination efforts based exclusively on MDA will not achieve disease elimination [7], whilst the consensus amongst experts (~70%) is that additional measures are required to eliminate human onchocerciasis [8]. The recent licencing of the macrocyclic lactone moxidectin for use as an additional microfilaricidal treatment is promising [9][10][11], whilst efforts to identify and evaluate safe drugs targeting adult worms (macrofilaricides) are ongoing [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…35 The lengthy therapy interval of 4-5 weeks and the contraindications for pregnant and breastfeeding women, as well as children below the age of 8 years led to the search for novel, faster acting drugs active against Wolbachia. 34,36 COR A constitutes one of these novel agents currently in the preclinical phase with the aim to develop it as a treatment for human larial infections (Fig. 1).…”
mentioning
confidence: 99%
“…Several new promising drugs for the treatment of onchocerciasis are being tested in clinical trials [ 11 , 12 ], of which moxidectin was shown to reduce and maintain low skin microfilarial density for longer than ivermectin [ 13 ]. Macrofilaricides, currently only in an early phase of development, will be needed to drastically reduce the elimination time of onchocerciasis [ 11 , 12 ]. However, today none of these new drugs are available for mass drug administration programmes.…”
Section: Introductionmentioning
confidence: 99%